Tummy Time and Development of 6- to 12-Month-Old Infants - Titah, Marvella Graceria; Surjono, Edward; Prabowo, Johanes A. C.; Setiawan, Andy; Dewi, Rita (Faculty of Medicine, Universitas Padjadjaran, 2025)
Early childhood development, particularly within the first 1,000 days of life, is a critical period. Globally, 5–16% of children experience developmental delays. This figure is higher in Indonesia with approximately 13–18% of children under five are facing growth and developmental issues. Adequate stimulation, including activities like tummy time, plays a vital role in a child's growth and development. This study aimed to investigate the correlation between tummy time and the developmental outcomes of infants aged 6–12 months. An analytical descriptive design with a cross-sectional approach was employed in this study that was conducted at Public Health Centers in North Sulawesi Province, Indonesia. Data collection involved questionnaires assessing the onset, frequency, and duration of tummy time, alongside the use of the Child Development Pre-Screening Questionnaire. With a minimum sample size of 96 respondents, data were analyzed using Spearman’s correlation. Findings indicated that performing tummy time more than 1–2 times per week, with each session lasting 6–20 minutes, was significantly associated with better developmental outcomes. However, no significant relationship was observed between early initiation of tummy time or the number of daily sessions with infant development. The study concluded that engaging in tummy time more than 1-2 times per week for 6-20 minutes per session can promote optimal infant development.